Intestinal parasites in segregated minority communities of Slovakia: results from a cross-sectional survey in children - Papajová, Ingrid; Bystrianska, Júlia; Giboda, Michal; Becker, Sören L; Utzinger, Jürg; Marti, Hanspeter (Acta tropica, 2021)
In Slovakia, the Roma population forms the second-largest ethnic minority. A large part of the Roma is semi-nomadic or lives in segregated settlements with poor living standards and limited access to health facilities. More than 40 years ago, a cross-sectional survey revealed a high prevalence of parasitic infections. There is a paucity of recent data, and hence, we designed a study to investigate the current status of intestinal parasitic infections in this population. Overall, 259 children aged 7 months to 18 years from 32 different segregated settlements provided faecal samples for microscopic examination using a sodium acetate-acetic acid-formalin concentration and the Paraprep L technique. Almost 40% of the samples yielded a positive result, with Ascaris lumbricoides (27.4%) and Giardia intestinalis (9.3%) being the most frequent helminth and intestinal protozoa species, respectively. Many children younger than 2 years were found to be infected, which suggests that community transmission is important. In view of our findings, there is a pressing need for targeted action to improve the health status of this neglected population.
Keywords: Cross-sectional survey; menšiny; formaldehyd; Infant; feces; Humans; Sodium acetate-acetic acid-formalin (SAF) concentration technique; Diagnosis; kojenec; giardiáza; dítě; prevalence; Child; Female; rizikové faktory; Ethnicity; lidé; Parasites; zvířata; Roma; mladiství; Paraprep L; Giardiasis; Slovenská republika; Slovakia; Feces; předškolní dítě; ženské pohlaví; Intestinal parasites; Male; helmintóza; Adolescent; Helminthiasis; Cross-Sectional Studies; Minority Groups; etnicita; Prevalence; Animals; mužské pohlaví; Child, Preschool; průřezové studie; Formaldehyde; paraziti; Risk Factors